Ideologi dalam Wacana Efisiensi Beasiswa KIP-Kuliah 2025 Kompas.com: Analisis Wacana Kritis Norman Fairclough - Putra, Muhammad Zanika Esa (STKIP PGRI Ponorogo Press, 2026)
This study aims to reveal the ideology embedded in the discourse of the 2025 KIP Kuliah scholarship budget efficiency as presented on the Kompas.com news portal. This research employs a qualitative method with an analytical approach based on Norman Fairclough’s model. Fairclough outlines three key dimensions in critical discourse analysis: (i) textual dimension, (ii) discourse practice dimension, and (iii) sociocultural dimension. The stages of data analysis include: (i) description process, (ii) interpretation process, and (iii) explanation process. The results indicate that the textual dimension contains ideologically loaded phrases and vocabulary such as cutting or reduction, not affected by budget efficiency, will not be reduced, restored, original, continued, and accessible. In the discourse practice dimension, Kompas.com employs moderate and rational word choices such as budget efficiency, budget adjustment, and program continuation. These lexical choices reflect an alignment with the state’s narrative emphasizing fiscal stability while simultaneously creating the impression that public interest is still being prioritized. In the sociocultural dimension, the news was written during a period when the KIP-Kuliah scholarship efficiency policy became a public concern. Institutionally, the report represents Kompas.com’s response to the issue, while the social aspect highlights the economic and educational impacts of the scholarship budget cuts on underprivileged communities.